Tolerance of wheat (Triticum aestivum) and triticale (xTriticosecale) to manganese deficiency - BANSAL, R L; NAYYAR, V K; THKKAR, P N (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during winter season (rabi) of 1988-89 to study the tolerance of 9 varieties of wheat (Triticum aestivum L. emend. Fiori & Paol.) and 1 variety of triticale (xTriticosecale Wittmack) on loamy-sand soil deficient in Mn. The varieties giving < 30, 30-55 aand > 55% increase ingrain yield of wheat compared with the control on Mn application were classified tolerant, moderately tolerant and least tolerant to Mn stress. The wheat varieties 'WL 1562'. 'PBW 34' and 'PBW 54' were rated least tolerant, and 'DWL 5023', 'WL 2265' and 'WL 711' moderately tolerant. A triticale variety 'TL 419' and 3 wheat varieties 'WL 410', 'HD 2329' and 'PBW 120' were rated Mn tolerant, as these had It much higher Mn uptake (213-248 g/ha) than the least tolerant varieties (97-138 g/ha). Grain yield was significantly related with both Mn concentration in flag-leaf (r = 0.69*) and Mn uptake (r = 0.86**) as well as harvest index (r = 0.68*).